Influence of Formal and Informal Institutions on Entrepreneurship - Pandey, Shivam Kumar (Digital Repository of Theses, 2025)
This study delves into how formal and informal institutions interact. Jointly influence the growth of entrepreneurship. It is based on a framework that compares elements such, as property rights, business freedom and financial resources with informal aspects like trust and culture. This research demonstrates how these combined factors can either support or impede entrepreneurship especially in rapidly expanding industries. Using a mixed methods approach the study explores how informal institutions work alongside regulations to either enhance or hinder entrepreneurial outcomes. The results show that the collaboration between formal and informal institutions is crucial for fostering opportunity- driven entrepreneurship and economic progress. This thesis advances discussions by outlining how these institutional dynamics impact high growth entrepreneurship providing insights for policymakers and stakeholders looking to create a conducive environment, for entrepreneurial prosperity and economic growth.